Does family structure affect children's educational outcomes? - Donna K. Ginther; Robert A. Pollak (Federal Reserve Bank of Atlanta, 2000)
In this paper we examine the effect of family structure on children's educational outcomes by exploiting the sibling structure in the NLSY and NLSY-Child to control for unobserved heterogeneity across families and individuals. We also compare outcomes for children within the same family—stepchildren with their half-siblings in the same blended family who are the biological children of both parents. Using panel data methods to control for unobserved heterogeneity across families, we find that family structure effects are statistically insignificant. Finally, comparing half-siblings in our data, we find no difference in educational outcomes as a function of family structure. Our empirical results are consistent with at least two interpretations. First, they can be interpreted as evidence that estimates of family structure effects reflect selection rather than causation. Second, they can be interpreted as evidence that the presence of stepchildren disrupts families.
Keywords: 330; Child care; Demography; Education; Human capital